'There's only so much you can be pushed': Magnification of the maternity staffing crisis by the 2020/21 COVID‐19 pandemic. (26th May 2022) - Cordey, Sarah; Moncrieff, Gill; Cull, Joanne; Sarian, Arni
Abstract : This article includes Author Insights, a video abstract available at: https://vimeo.com/bjogabstracts/authorinsights17203